Chemical and Structural Analysis of Newly Prepared Co-W-Al Alloy by Aluminothermic Reaction - Michna, Štefan; Knaislová, Anna; Hren, Iryna; Novotný, Jan; Michnová, Lenka; Svobodová, Jaroslava (Materials, 2022)
This article is devoted to the characterization of a new Co-W-Al alloy prepared by an aluminothermic reaction. This alloy is used for the subsequent preparation of a special composite nanopowder and for the surface coating of aluminum, magnesium, or iron alloys. Due to the very high temperature (2000 °C–3000 °C) required for the reaction, thermite was added to the mixture. Pulverized coal was also added in order to obtain the appropriate metal carbides (Co, W, Ti), which increase hardness, resistance to abrasion, and the corrosion of the coating and have good high temperature properties. The phase composition of the alloy prepared by the aluminothermic reaction showed mainly cobalt, tungsten, and aluminum, as well as small amounts of iron, titanium, and calcium. No carbon was identified using this method. The microstructure of this alloy is characterized by a cobalt matrix with smaller regular and irregular carbide particles doped by aluminum.